Covid 19 Natural Evil / Human Evil: A Philosophical Investigation - Uzommah Michael; Anselm Ikenna Odo; Nwohah Petermary (Program Studi Sosiologi, 2021)
This paper sought to find out whether COVID 19 is as a result of natural evil, human evil or both. The researchers adopt an expository method in carrying out this work. Viruses have been around in the world long as life itself. We can confidently say that life as we know it would not exist without viruses. Viruses do leave “fossils” in the Deoxyribonucleic Acid (DNA)-the hereditary material in humans and of other organisms, from which their history can be reconstructed. It is as a result of this that the researchers posit that COVID 19 is neither natural evil nor human evil. The researchers conclude that the issue of COVID 19 outbreak ravaging the earth has a sufficient reason. But sometimes our emotions blind us from seeing the reason but solely the event.